Reaction of Dimethyl Sulfoxide-Acetic Anhydride with 4-Hydroxy-coumarin and Its Derivatives Under Microwave Conditions - Qadir, Saima; Zaman Khan, Khaliquz; Jan, Arif (Asian Journal of Chemistry, 2013)
4-Hydroxycoumarin and various biscoumarins synthesized under microwave conditions were treated with the DMSO-Ac2O reagent under the same conditions to yield different products. A comparative account of the reactions with conventional procedure, as reported in literature, has been drawn and improved yields have been obtained in minimum time under microwave conditions for the first time.